2002
DOI: 10.4269/ajtmh.2002.66.686
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of thrombocytopenia in African children with falciparum malaria.

Abstract: Abstract. Thrombocytopenia is a common finding in malaria, but its prognostic value has not been addressed in children. The relationship between thrombocytopenia (platelet count < 100,000/mm 3 on admission) and severity and outcome was investigated prospectively in children hospitalized with falciparum malaria in Dakar, Senegal, an area that is hypoendemic for malaria. Of 288 falciparum cases, 215 matched the 2000 World Health Organization definition of severe malaria. Median platelet counts were lower (98,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
122
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(153 citation statements)
references
References 24 publications
22
122
3
1
Order By: Relevance
“…The reason for rare bleeding episodes in malaria may be the hypersensitive platelets, which are thought to enhance haemostatic responses which have been reported despite thrombocytopenia 11,12,13 . In a study by Chandra 14 the MPV of more than 8fL was a comparatively more sensitive indicator for vivax malaria (70.8%) than falciparum (50.4%).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for rare bleeding episodes in malaria may be the hypersensitive platelets, which are thought to enhance haemostatic responses which have been reported despite thrombocytopenia 11,12,13 . In a study by Chandra 14 the MPV of more than 8fL was a comparatively more sensitive indicator for vivax malaria (70.8%) than falciparum (50.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have identifi ed a relationship between the decrease in PC and the appearance of clinical complications, such as anemia, respiratory distress syndrome and cerebral malaria 37 . We found that the patients with severe (25,000-49,999 platelets/µL) or profound thrombocytopenia (<25,000 platelets/µL) had more pathological changes in their clinical status compared with the patients without thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia can be interpreted as evidence of damage and has been associated with clinical complications and high parasitemia 9,12,37 . However, some studies have suggested that thrombocytopenia has a protective effect, which reduces the probability of red blood cell aggregation 28 or mediates parasite destruction.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that fibrin, monocytes, and platelets accumulate in the brain of patients who died from CM* abstract 39 indicating that these vessels display a proinflammatory/ -coagulant environment. Actually, platelets may contribute to malaria pathogenesis through exposure of PS and release of pro-inflammatory mediators among other mechanisms 20 ; besides, one study concluded that trombocytopenia have predictive value for mortality in P. falciparum-infected patients 12 .…”
Section: The Tissue Factor Model For Malaria Pathogenesismentioning
confidence: 99%
“…The main argument that supports this notion is the fact that the vast majority, perhaps all patients with mild and severe malaria, present elevated levels of D-dimers20, a specific marker of plasmin-mediated fibrin proteolysis in vivo 23 . Finally, it has been reported that hemostatic alterations correlate with parasitemia, thrombocytopenia, and/or severity of P. falciparum infection in a number of studies; in addition, antiparasitic treatment halts the coagulation disorder and improves clinical outcome [12][13][14][15][16][17][18][19][20] .Therefore, it is plausible that hemostatic alterations play a role in the disease progression and organ failure observed in malaria 16,20 .More recently, it has been demonstrated that P. falciparum-parasitized RBC (pRBC) induce tissue factor (TF) expression in the microvascular EC in vitro, and support the assembly of multimolecular coagulation complexes 10 . TF is the clotting initiator 24-26 and a structural member of the cytokine receptor family, which signifies the expansion of the adaptive immune system in vertebrates, indicating a close connection of the coagulation pathways with the host response to infection 27 .…”
mentioning
confidence: 99%